Direct and indirect landscape effects on Quercus ilex regeneration in heterogeneous environments. (Oecologia, 2012)
Understanding how plant-animal interactions shape plant regeneration is traditionally examined at local scales. In contrast, landscape ecologists working at regional scales often have to infer the mechanisms underlying vegetation patterns. In this study, we empirically explored how landscape attributes (patch connectivity, size, shape, irradiance, slope, and elevation) influence biotic interactions in 1- and 2-year seedlings and saplings of Quercus ilex. We combined field data and GIS-based information under a set of five connectivity scenarios, presuming low, intermediate, and long-distance seed dispersal. Our study emphasizes that landscape, apart from its direct effects on plants, plays a key, albeit indirect, role in plant demography through its effects on seed dispersers and predators. Moreover, the effects of landscape on recruitment differed between plant life stages. One-year seedlings and saplings appear to depend more on plant-animal interactions, while 2-year seedlings depend more on irradiance. Differences in patch connectivity resulted in direct and indirect effects on biotic interactions, which, in turn, produced contrasting positive and negative effects on regeneration at different stages of the life cycle. While jays and wild boars seem crucial to all life stages and most of the connectivity scenarios, rodents and herbivores affected only 1-year seedlings and saplings, respectively, and only a few of the connectivity scenarios. By simultaneously including an ensemble of explanatory factors, our study emphasizes that regeneration depends on a set of key drivers, both abiotic (i.e. irradiance) and biotic (i.e. jays and wild boars), whose effects are greatly modulated by landscape traits.

Comparing the role of site disturbance and landscape properties on understory species richness in fragmented periurban Mediterranean forests (Landscape Ecology, 2007)
We hypothesized that the spatial con- ﬁguration and dynamics of periurban forest patches in Barcelona (NE of Spain) played a minor role in determining plant species richness and assemblage compared to site conditions, and particularly to both direct (measured at plot level) and potential (inferred from landscape metrics) human-associated site disturbance. The presence of all understory vascular plants was recorded on 252 plots of 100 m 2 randomly selected within forest patches ranging in size from 0.25 ha to 218 ha. Species were divided into 6 groups, according to their ecology and conservation status. Site condition was assessed at plot level and included physical attributes, human-induced disturbance and Quercus spp. tree cover. Landscape structure and dynamics were assessed from patch metrics and patch history. We also calculated a set of landscape metrics related to potential human accessibility to forests. Results of multiple linear regressions indicated that the variance explained for non-forest species groups was higher than for forest species richness. Most of the main correlates corresponded to site disturbance variables related to direct human alteration, or to landscape variables associated to indirect human effects on forests: Quercus tree cover (a proxy for successional status) was the most important correlate of non-forest species richness, which decreased when Quercus tree cover increased. Human-induced disturbance was an important correlate of synanthropic and total species richness, which were higher in recently managed and in highly frequented forests. Potential human accessibility also affected the richness of most species groups. In contrast, patch size, patch shape and connectivity played a minor role, as did patch history. We conclude that human inﬂuence on species richness in periurban forests takes place on a small scale, whereas large-scale effects attributable to landscape structure and fragmentation are comparatively less important. Implications of these results for the conservation of plant species in periurban forests are discussed.

Comparing the role of site disturbance and landscape properties on understory species richness in fragmented periurban Mediterranean forests - Guirado, Maria; Pino, Joan; Rodà, Ferran (Landscape Ecology, 2007)
We hypothesized that the spatial con- ﬁguration and dynamics of periurban forest patches in Barcelona (NE of Spain) played a minor role in determining plant species richness and assemblage compared to site conditions, and particularly to both direct (measured at plot level) and potential (inferred from landscape metrics) human-associated site disturbance. The presence of all understory vascular plants was recorded on 252 plots of 100 m 2 randomly selected within forest patches ranging in size from 0.25 ha to 218 ha. Species were divided into 6 groups, according to their ecology and conservation status. Site condition was assessed at plot level and included physical attributes, human-induced disturbance and Quercus spp. tree cover. Landscape structure and dynamics were assessed from patch metrics and patch history. We also calculated a set of landscape metrics related to potential human accessibility to forests. Results of multiple linear regressions indicated that the variance explained for non-forest species groups was higher than for forest species richness. Most of the main correlates corresponded to site disturbance variables related to direct human alteration, or to landscape variables associated to indirect human effects on forests: Quercus tree cover (a proxy for successional status) was the most important correlate of non-forest species richness, which decreased when Quercus tree cover increased. Human-induced disturbance was an important correlate of synanthropic and total species richness, which were higher in recently managed and in highly frequented forests. Potential human accessibility also affected the richness of most species groups. In contrast, patch size, patch shape and connectivity played a minor role, as did patch history. We conclude that human inﬂuence on species richness in periurban forests takes place on a small scale, whereas large-scale effects attributable to landscape structure and fragmentation are comparatively less important. Implications of these results for the conservation of plant species in periurban forests are discussed.
Keywords: Forest condition; Forest fragmentation; Forest patches; Human-induced disturbance; Multiple linear regressions; Patch history; Plant species richness; Synanthropic species

Quercus and Pinus cover are determined by landscape structure and dynamics in peri-urban Mediterranean forest patches (Plant Ecology, 2007)
Successional dynamics in Mediterranean forests have been modulated by anthropogenic disturbances during thousands of years, especially in areas densely populated since ancient times. Our objective is to determine whether pine tree cover (early-successional species) and oak tree cover (late-successional species), used as a surrogate of successional stage of peri-urban fragmented forests in the Valle`s lowlands (Catalonia, NE, Spain), are primarily determined by (1) climate and topography; (2) anthropogenic disturbances; (3) patch structure; or (4) patch dynamics from 1956 to 1993. Quercus spp. and Pinus spp. tree cover were separately recorded on 252 randomly selected plots of 100 m 2 , within forest patches ranging in size from 0.25 to 218 ha. Multiple linear regressions indicated that forest patch history is the most important variable determining oak and pine tree cover: new forest patches showed higher pine and lower oak tree cover than recently split patches (i.e. those that became fragmented from large forest areas after 1956). Patches already existing as such in 1956 (pre-existent patches) showed higher pine cover than recently split patches. Oak cover increased and pine cover decreased with increasing forest connectivity of the patch. Finally, highly frequented forests were related to high cover of pines. Climatic and topographic variables were not signiﬁcant. We conclude that pine and oak cover in these peri-urban forests are mainly determined by recent patch dynamics, but also by the spatial pattern of patches. However, humaninduced disturbance can modulate this as there is some evidence for pine being associated with a high human frequentation.

Large-scale environmental correlates of forest tree distributions in Catalonia (NE Spain) (Global Ecology and Biogeography, 2003)
Aim To explore the environmental correlates of tree species distributions in Catalonia according to the chorological status of the species. Location The study area is the region of Catalonia, in northeastern Spain. Methods We used presence-absence data for 24 species, sampled in random plots distributed throughout forests of Catalonia. A climate model for the Catalonia region provided environmental variables. We used classiﬁcation tree analysis to explore the environmental correlates of the realized niches of tree species. The predictive accuracy of the models was assessed using the ROC curve approach. Potential distribution maps of tree species were generated for the whole Catalonia region. Results Models were ranked from low to high accuracy for the 24 species. Differences in accuracy among species were related to the chorological status of species. Zonal species, or species at the core of their range (Mediterranean and SubMediterranean species), were generally well predicted, while extrazonal species, or species at the edge of their range, were predicted only moderately well. Mediterranean species distributions showed good correlations with extreme temperatures and annual precipitation. Main conclusions The above trends conﬁrmed the difﬁculty of identifying the realized niche of species at the edges of their ranges. In contrast, Mediterranean and Sub-Mediterranean species, which were at the core of their range, were well-predicted, conﬁrming the importance of extremes of temperature and annual precipitation as effective surrogates for variables having more direct physiological roles in limiting the ability of plants to survive and grow. Maps of potential tree distributions allowed us to deﬁne suitable habitats and to highlight areas where species have been planted outside their natural distribution.

Large-scale environmental correlates of forest tree distributions in Catalonia (NE Spain) - Thuiller, Wilfried; Vayreda, Jordi; Pino, Joan; Sabaté, Santi; Lavorel, Sandra; Gracia, Carles (Global Ecology and Biogeography, 2003)
Aim To explore the environmental correlates of tree species distributions in Catalonia according to the chorological status of the species. Location The study area is the region of Catalonia, in northeastern Spain. Methods We used presence-absence data for 24 species, sampled in random plots distributed throughout forests of Catalonia. A climate model for the Catalonia region provided environmental variables. We used classiﬁcation tree analysis to explore the environmental correlates of the realized niches of tree species. The predictive accuracy of the models was assessed using the ROC curve approach. Potential distribution maps of tree species were generated for the whole Catalonia region. Results Models were ranked from low to high accuracy for the 24 species. Differences in accuracy among species were related to the chorological status of species. Zonal species, or species at the core of their range (Mediterranean and SubMediterranean species), were generally well predicted, while extrazonal species, or species at the edge of their range, were predicted only moderately well. Mediterranean species distributions showed good correlations with extreme temperatures and annual precipitation. Main conclusions The above trends conﬁrmed the difﬁculty of identifying the realized niche of species at the edges of their ranges. In contrast, Mediterranean and Sub-Mediterranean species, which were at the core of their range, were well-predicted, conﬁrming the importance of extremes of temperature and annual precipitation as effective surrogates for variables having more direct physiological roles in limiting the ability of plants to survive and grow. Maps of potential tree distributions allowed us to deﬁne suitable habitats and to highlight areas where species have been planted outside their natural distribution.
Keywords: chorology; classification tree analysis; environmental gradients; forest trees; potential distribution maps; realized niche; Spain